2009
DOI: 10.54386/jam.v11i2.1240
|View full text |Cite
|
Sign up to set email alerts
|

Light interception and radiation use efficiency of wheat varieties as influenced by number of irrigations

Abstract: An experiment was conducted during rabi seasons of 2002-03 and 2003-04 to quantify the light interception and radiation use efficiency for three wheat varieties as affected by variable number of irrigations with the combination of three wheat varieties viz., HUW-234, HD-2285 and PBW-154. The light interception increased successively till 90 days after sowing (DAS) and thereafter a gradual decrease was observed till maturity of the crop. Four irrigations given at CRI, late tillering, late jointing and ear head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…PGP bacteria mitigate the salinity damage in several crops through various mechanisms, including improved water uptake and osmolyte accumulation (glutamate, glycine betaine, proline and soluble sugars). Also, PGP bacteria increases antioxidant levels, synthesis of ACC deaminase, exopolysaccharides production and ionic homeostasis, which in turn enhances agricultural productivity even in saline-alkaline soil (Mishra et al, 2023). Currently, studies in various parts of the world are reporting improvements in the growth and production of crops such as tomatoes (Fan et al, 2016;Astorga-Elóet al, 2021), maize (Ojuederie and Babalola, 2023), and wheat (Shankar and Prasad, 2023), attribute to the use of PGP bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGP bacteria mitigate the salinity damage in several crops through various mechanisms, including improved water uptake and osmolyte accumulation (glutamate, glycine betaine, proline and soluble sugars). Also, PGP bacteria increases antioxidant levels, synthesis of ACC deaminase, exopolysaccharides production and ionic homeostasis, which in turn enhances agricultural productivity even in saline-alkaline soil (Mishra et al, 2023). Currently, studies in various parts of the world are reporting improvements in the growth and production of crops such as tomatoes (Fan et al, 2016;Astorga-Elóet al, 2021), maize (Ojuederie and Babalola, 2023), and wheat (Shankar and Prasad, 2023), attribute to the use of PGP bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes associated with the mangrove are known to tolerate high salinity. Several studies have demonstrated that bacterial isolates from mangrove sediments and rhizosphere have PGP potentials, make them potential sources for isolating PGP strains (Mishra et al, 2023).…”
Section: Introductionmentioning
confidence: 99%